1990
DOI: 10.1002/pssb.2221600227
|View full text |Cite
|
Sign up to set email alerts
|

Point Defects in Electron‐Irradiated Stoichiometric Magnetite

Abstract: High‐purity, stoichiometric, single crystalline magnetite (Fe3O4) has been electron (e−)‐irradiated below 45 K to a dose of 1023 electrons/m2. Radiation‐induced point defects give rise to both drastic modifications of intrinsic electronic processes and the occurrence of reorientation‐type magnetic relaxations. Both phenomena offer deeper insights into the mechanisms of (i) electronic charge transport and (ii) thermally activated reactions of interstitials and vacancies. Coordination between migration of elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 35 publications
(83 citation statements)
references
References 27 publications
7
76
0
Order By: Relevance
“…Fig. 1a, b [4,13]. On the other hand, fitting was still possible in this crystal for the respective hopping plateau, despite its typically defect-induced modifications [4 to 11], i.e.…”
Section: Electronic Low-temperature Processesmentioning
confidence: 87%
See 3 more Smart Citations
“…Fig. 1a, b [4,13]. On the other hand, fitting was still possible in this crystal for the respective hopping plateau, despite its typically defect-induced modifications [4 to 11], i.e.…”
Section: Electronic Low-temperature Processesmentioning
confidence: 87%
“…Thus, it has been suggested that e.g. in the above-mentioned compounds, due to alternatively induced stresses intrinsic interstitials, too, may have formed giving rise, similarly as in e À -irradiated magnetite, to the reorientationtype process IV near 200 K [6,11,13].…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most fascinating features of this study was the observation of an intermediate transformation of the initial radiation-damaged low-temperature (T < 60 K) spectrum, after annealing to a temperature of T a ¼ 523 K, into a structure resembling that of the wellknown low-temperature spectrum of undisturbed, stoichiometric magnetite (Fe 3 O 4 ), [2][3][4][5], cf. Figs.…”
Section: Introductionmentioning
confidence: 84%